2009
DOI: 10.1039/b9nr00102f
|View full text |Cite
|
Sign up to set email alerts
|

One-pot formation of SnO2 hollow nanospheres and α-Fe2O3@SnO2 nanorattles with large void space and their lithium storage properties

Abstract: In this work, uniform SnO(2) hollow nanospheres with large void space have been synthesized by a modified facile method. The void space can be easily controlled by varying the reaction time. The formation of interior void space is based on an inside-out Ostwald ripening mechanism. More importantly, this facile one-pot process can be extended to fabricate rattle-type hollow structures using alpha-Fe(2)O(3)@SnO(2) as an example. Furthermore, the electrochemical lithium storage properties have been investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
155
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(160 citation statements)
references
References 33 publications
4
155
1
Order By: Relevance
“…As the reaction proceeds, recrystallization of more small crystallites from the interior in the outer shell region leads to an enlarged hollow interior space accompanied by construction of a compact shell (hollowing effect). [23] Subsequently, the large nanoparticles gradually evolve into hollow nanospheres by self-assembly due to a combination of classical Ostwald ripening and a nonclassical particle-based crystallization process with increasing reaction time. Surface energy is a possible driving force for the self-assembly of SnO 2 nanocrystals in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…As the reaction proceeds, recrystallization of more small crystallites from the interior in the outer shell region leads to an enlarged hollow interior space accompanied by construction of a compact shell (hollowing effect). [23] Subsequently, the large nanoparticles gradually evolve into hollow nanospheres by self-assembly due to a combination of classical Ostwald ripening and a nonclassical particle-based crystallization process with increasing reaction time. Surface energy is a possible driving force for the self-assembly of SnO 2 nanocrystals in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…At high potential, SnO 2 can also help to buffer the volume change of α‐Fe 2 O 3 . In addition, the transition metal Fe produced during the lithiation reaction of α‐Fe 2 O 3 had a catalytic function to promote the first backward reaction of SnO 2 124, 125…”
Section: Self‐supported Metal Oxide Nanoarrays On 2d Planar Substratesmentioning
confidence: 99%
“…SnO 2 -based composites have been studied before, [10][11][12] but the authors only reported a "synergistic effect" in quite vague terms. No one has ever realized the catalyzed oxidation of the tin metal or provided any direct evidence.…”
Section: Introductionmentioning
confidence: 97%